Airway sensory systems: breathing new life into microbiota-brain communication - Mann-Nüttel, Ritu; Armbruster, Marie; Mandal, Shivani; Forsythe, Paul (Frontiers in Cellular Neuroscience, 2025)
The essential role of the lungs in gas exchange necessitates exposure to possible threats from a dynamic external environment. To protect life-critical functions the airways contain multiple systems that monitor the inhaled environment and elicit appropriate defensive responses. As such the airways represent a key sensory surface with multiple signaling pathways to the brain. Despite the presence of rich and diverse bacterial communities in both upper and lower airways, the respiratory tract has been relatively overlooked compared to the gut regarding its potential as an interface between microbes and the central nervous system. This review draws attention to the respiratory system, specifically the nasal cavity and lungs, and the evidence supporting a microbiota-airway-brain axis. We highlight the olfactory system and the role of the lungs as a sensory organ, monitoring the inhaled environment, as clear examples of airway-brain communication and identify how these communication pathways can be engaged by microbes. We also outline the relationship between the airways and mental health and present the case that the nasal and lung microbiota should be considered alongside that of the gut as potential influencers of brain function, mood, and behavior.